Study on Clinical Manifestations Of Biliary Ascariasis Patients in Sadar Hospital, Cox’s Bazar (Journal of Dhaka Medical College, 2023)
Aims: Aim of the study was to know the clinical presentations of biliary ascariasis.Materials and Methods: It was a cross-sectional observational study had been carried out on 50 patients over a period from January 2017 to December 2018 at the Department of Medicine, Sadar Hospital, Cox’s bazar. The clinical presentation, ultrasonographic findings, management and follow up of patients diagnosed to have biliary ascariasis were recorded in a pre-designed case record form and finally all the relevant data were processed and analyzed.Results: This study revealed that maximum patients of biliary ascariasis belonged to 31-40 yrs age group. Number of female patients was more (86%) in comparison to male patients (14%). Among female patients, 20.93% patients were pregnant. Most of the patients 92%came from rural areas. All patients in this study presented with upper abdominal pain. Other complaints were nausea, vomiting, fever and jaundice. Most of the patients (38%) had history of passage of worm with vomitus. Ultrasonographic profile of this study revealed that ascaris was most commonly entrapped in the common bile duct (80%). The percentage of complications was 38%. Acute acalculous cholecystitis was the commonest. The percentage of Cholangitis and acute pancreatitis was also significant.Conclusion: Bangladesh is an endemic zone for ascaris lumbricoides infestations. Ultrasonography is the investigation of choice for diagnosis and follow up of the patient of biliary ascariasis. Majority of the patient can be managed with conservative treatment and mechanical removal of worms by endoscopy. This study recommends that proper hygiene and regular deworming can prevent biliary ascariasis.J Dhaka Med Coll. 2021; 29(1): 87-93